Organized labor versus robots? Evidence from micro data - Sebastian Findeisen; Wolfgang Dauth; Oliver Schlenker (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
New technologies drive productivity growth but the distribution of gains might be unequal and is mediated by labor market institutions. We study the role that organized labor plays in shielding incumbent workers from the potential negative consequences of automation. Combining German individual-level administrative records with information on plant-level robot adoption and the presence of works councils, a form of shop-floor worker representation, we find positive moderating effects of works councils on retention for incumbent workers during automation events. Separations for workers with replaceable task profiles are significantly reduced. When labor markets are tight and replacement costs are high for firms, incumbent workers become more valuable and the effects of works councils during automation events start to disappear. Older workers, who find it more challenging to reallocate to new employers, benefit the most from organized labor in terms of wages employment. Concerning mechanisms we find that robot-adopting plants with works councils employ not more but higher quality robots. They also provide more training during robot adoption and have higher productivity growth thereafter.
urn:nbn:de:bsz:352-2-pkkgn822nr6u9
Keywords: J20; J30; J53; O33; 320; automation; organized labor; work councils; labor market tightness; worker re-training